YENİ BİR İLMİ KELAM PROJESİ OLARAK BAĞLAMSAL TEOLOJİ - Metin Özdemir (İslami İlimler Dergisi)
The aim of this article is to emphasize the position and the importance of the contextual theology that based on the contextual reading in the projects of new ilm al-kalam. We can say that the finding of each one from the Kalam schools a support from the Quran easily for theirs contradictory assertions which connected with the same subject is due to their desertion of the contextual reading and their evaluation either a verses completely or partially. For they have thought it would be a base for theirs assertions on a theoretical ground. Thus, we have tried in this article to touch on the advantages of the contextual theology that based on the contextual reading, as a Project of the new ilm al-kalam, whit a view to rid of this difficult. Because we believe that, this is one of the useful methods for escaping from the difficult that marked above.